Seed-borne Fungi of Soybean (Glycine max (L.) Merril) and their control. - Wan Nik, Wan Zainun (1980)
Fungi associated with seed of 14 cultivars comprising 16 samples of soybean were investigated and 27 species were isolated. Pathogenic fungi frequently isolated were Botryodiplodia theobromae, Colletotrichum dematium, Diaporthe phaseolorum, Choanephora cucurbitarum, Fusarium equiseti, F. fusarioides, F. moniliforme, F. semitectum, Macrophomina phaseolina, Myrothecium roridum, and Phoma sorghina. Other fungi isolated included species of Aspergillus, Chaetomium, Cladosporium, Curvularia, Nigrospora, odulisporium, Penicillium, Rhizopus, Trichoderma and Zygosporium. Seeds which were treated with fungicides had a higher germination in vitro compared to the control. Benomyl eliminated most of the pathogenic fungi associated with soybean seeds